Magkukuwento na si Lola: Ang Mga Kuwento ni Lola Basyang sa Libro, Teatro, Telebisyon, at Radyo - Bellen, Christine S. (Plaridel Journal of Communication, Media, and Society, 2011)
This paper analyzes how the popular stories of Severino Reyes have been translated into various forms of media. After Gilda Cordero-Fernando translated the story into English in 1997 for Tahanan Books, Lola Basyang stories became even more a part of children's literature. On the other hand, the publication of Lola Basyang picture books in 2004-2005 and 2007 paved the way for the stories to be adapted for dance, theater, television, and radio. Each of these media required different ways of adapting the classic stories.